Internal mammary node irradiation in node-positive breast cancer treated with mastectomy and taxane-based chemotherapy. (October 2021) - Cho, Won Kyung; Chang, Jee Suk; Park, Seung Gyu; Kim, Nalee; Choi, Doo Ho; Kim, Haeyoung; Kim, Yong Bae; Park, Won; Suh, Chang Ok
Abstract: Background: It is important to continually reevaluate the risk/benefit calculus of internal mammary node irradiation (IMNI) in the era of modern systemic therapy. We aimed to investigate the effect of IMNI on survival in node-positive breast cancer treated with mastectomy and anthracycline plus taxane-based chemotherapy. Methods: We analyzed 348 patients who underwent mastectomy and anthracycline plus taxane-based chemotherapy for node-positive breast cancer between January 2006 and December 2011. All patients received postoperative radiation therapy (RT) with IMNI ( n = 105, 30.2%) or without IMNI ( n = 243, 69.8%). The benefit of IMNI for disease-free survival (DFS) and overall survival (OS) was evaluated using multivariate analysis and inverse probability of treatment weighting (IPTW) to adjust for unbalanced covariates between the groups. Results: After a median follow-up of 95 months, the 10-year locoregional recurrence-free survival rate, DFS, and OS in all patients were 94.8%, 77.4%, and 86.2%, respectively. The IPTW-adjusted hazard ratio (HR) for the association of IMNI (vs. no IMNI) with DFS and OS was 0.208 (95% confidence intervals (CI) 0.045–0.966) and 0.460 (95% CI, 0.220–0.962), respectively. In multivariate analysis, IMNI was a favorable factor for DFS (HR, 0.458; P = 0.021) and OS (HR 0.233, P = 0.018). Conclusions: IMNI was associated with improved DFS and OS in node-positive patients treated with mastectomy, post-mastectomy RT, and taxane-based chemotherapy, although the rate of locoregional recurrence was low. Highlights: We evaluated the benefit of IMNI in modern era. In taxane-based chemotherapy era, locoregional recurrence was very low (5.2%) in node-positive breast cancer. IMNI was associated with improved survival.